2019
DOI: 10.4103/ijpsym.ijpsym_123_19
|View full text |Cite
|
Sign up to set email alerts
|

Women with Mental Illness - An Overview of Sociocultural Factors Influencing Family Rejection and Subsequent Institutionalization in India

Abstract: Background: Family abandonment and rejection resulting in homelessness are detrimental to women diagnosed with mental illness in India. A majority of the literature related to homelessness holds a western background, and women's homelessness in relation to mental illness is relatively unexplored in the Indian context. This review was conducted to understand the sociocultural factors influencing family rejection and to synthesize the living situation of institutionalized women with mental illness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 15 publications
(29 reference statements)
1
14
0
Order By: Relevance
“…31 Scholars have also reported that this feeling of worthlessness arises when individuals with schizophrenia experience abandonment by their family for any reason. 1,32,33 Notably, some participants' perceptions were influenced by defective insights into their diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…31 Scholars have also reported that this feeling of worthlessness arises when individuals with schizophrenia experience abandonment by their family for any reason. 1,32,33 Notably, some participants' perceptions were influenced by defective insights into their diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Mental illness is a major factor that can contribute to homelessness and can also significantly impact health. 32 In western countries, the prevalence of mental illness among the homeless population, including psychotic illnesses and personality disorders, is higher compared to the age-matched general population in those countries. 34 Homeless mentally-ill women are one of the most deprived populations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that underserved women face a myriad of different health challenges that are the result of factors, including low SES, governmental policies, mental illness, and low education levels. [31][32][33] These factors not only contribute to homelessness and being underserved, but may also impact a woman's health. 31,33 Homeless women are more likely to have lower levels of education, suffer from poor mental health, and be undernourished.…”
Section: Discussionmentioning
confidence: 99%
“…Again, self-perception in this study was the feeling of uselessness through rejection or abandonment in the hospital. According to Loh (2018), Hasan and Adil (2019), and Moorkath et al (2019), the feeling of uselessness, is the reactions individuals with schizophrenia experience from family. Moorkath et al (2019) discovered that families abandon relatives with schizophrenia for many reasons ranging from avoidance of labelling of the family name, to burden of care and feeling of hopelessness.…”
Section: Discussionmentioning
confidence: 99%
“…According to Loh (2018), Hasan and Adil (2019), and Moorkath et al (2019), the feeling of uselessness, is the reactions individuals with schizophrenia experience from family. Moorkath et al (2019) discovered that families abandon relatives with schizophrenia for many reasons ranging from avoidance of labelling of the family name, to burden of care and feeling of hopelessness. Hasan and Adil (2019) stated families abandon people with schizophrenia to protect their social outlook and financial status.…”
Section: Discussionmentioning
confidence: 99%